Resource allocation in hierarchical distributed EHR system based on improved poly-particle swarm - Chunzhong Xia; Shunlin Song (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
A hierarchical distributed EHR (Electronic Health Record) integration model HDEHR is proposed to solve the problems in tradition centralized EHR integration model. The architecture of HDEHR and the ways how it synchronizes, retrieves and accesses EHR data is introduced. The system resource allocation problem in HDEHR is given and the problem formulation is built. A reconcile model of minimum average waiting time and maximum entropy is proposed for solving the nonlinear programming problem. An improved poly-particle swarm algorithm is designed according to the hierarchical characteristic of HDEHR model and used to solve the optimization problem of resource allocation. The simulation experiments show that the system has a linear response capability and can solve the bottleneck problem in centralized EHR model.